The Role of Virtual Laboratories in Improving Students' Learning Motivation - Baiq Anisya Nelahi Purnadya; Baiq Oriza Januarlinda; Nurul Asmaya Fitria Hasanah; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2023)
Virtual laboratories have emerged as a pivotal innovation in modern science education, yet a synthesized understanding of their psychological impact remains limited. This study examines the role of virtual laboratories in enhancing student learning motivation using a systematic literature review approach. A total of 18 research articles published between 2014 and June 2023 were analyzed. The literature selection process followed rigorous identification, screening, eligibility, and inclusion stages based on predetermined criteria. Data were synthesized using a thematic analysis approach, categorizing the findings into three primary themes: learning motivation, student engagement, and conceptual understanding. The findings indicate that virtual laboratories significantly boost student learning motivation by providing interactive, flexible, and immersive learning experiences. Additionally, these digital platforms facilitate the visualization of abstract concepts, thereby fostering student participation and curiosity. Consequently, virtual laboratories serve as an effective and innovative tool capable of transforming contemporary science education.